Performance-Related Medical Problems of University Jazz Studies Majors. Issue 1 (2nd January 2016) - Devroop, Karendra
ABSTRACT: Over the past 30 to 40 years there has been a growing body of research on the medical problems of musicians and the broader arts community. This highly specialized and innovative field has garnered international recognition with the establishment of clinical settings that address musician health in several countries, institutions focusing on research and education and an expanding body of research studies. While several studies have looked at specific populations such as classical musicians, non-classical musicians, professional musicians and student musicians, no studies were found that specifically targeted university jazz studies majors. Accordingly, the purpose of this study was to investigate the performance related medical problems of university level jazz studies majors. Results indicated that a little over a quarter of the responding group indicated they experienced performance related medical problems with a mean pain-severity level of 3.58 ( SD = 2.68) on a range of 1 to 10. Performance related medical problems appeared to be higher for younger musicians and tended to decrease with age. Medical problems were specific to the various instrument types under investigation.